Relação da influência dos sintomas comportamentais e psicológicos no comprometimento cognitivo leve e na demência leve e moderada em idosos da estratégia saúde da família do município de Porto Alegre - Finger, Geisa (2016)
The behavioral and psychological symptoms of dementia (BPSD), has been a concern among mental health services due to the high injury rate in functionality and quality of life of this population. However, still remains open understanding of the psychological and behavioral changes that characterize each stage of cognitive decline. This study aimed to evaluate each SCPD present in the Neuropsychiatric Inventory (NPI) in elderly patients with mild cognitive decline, mild and moderate dementia, and relate to gender, age, educational level and degree of cognitive decline. Methods: Cross-sectional descriptive and analytical study with retrospective data collection of 123 elderly from Pontifical Catholic University of Rio Grande does Sul (PUC-RS). Data were collected from medical records of patients submit the following completed instruments: (i) Cognitive Examination Addenbrooke (ACE-R); (ii) Clinical Staging of Dementia (CDR); (iii) the Neuropsychiatric Inventory (NPI). The description of variables was being conduct using frequencies, means and standard deviations. The association between categorical variables (gender, education, age and CDR) and the presence of behavioral and psychological symptoms will be analyzed. P values ≤ 0.05 will be considered significant. In assessing the association of the BPSD with sex, apathy showed a significant association (p = 0.027) in 44.4% of men and eating disorders (p = 0.019). The association of the BPSD and age, delusions corresponded to 13.3% in the age group of 60 to 69 years, 9.4% between 70 and 79 years and 32.5% after 80 years of age (p = 0.024). Depression was present in 66.7% of individuals between 60 to 69 years, 52.8% between 70-79 years and 42.5% in octogenarians (p = 0.047). In the association of the BPSD with education, delusions were present in 23.7% of the population illiterate or with up to 3 years of schooling, 11.4% between 4 and 7 years of study, no cases above 80 years of age (p = 0.021). Anxiety showed 32.9% in illiterate individuals or up to 3 years of study, 54.3% in those aged 4 to 7 years of study and 58.3% when above 8 years of study (p = 0.020). The euphoria was not present in illiterate and showed values of 8.6% in those with 4-7 years of schooling and 8.3% over 8 years of education (p = 0.019). By analyzing the association of the BPSD in relation to cognitive decline, delusions presented significant data with 5.0% in mild cognitive decline, 18.2% in mild dementia and 35.7% in moderate dementia (p = 0.001). Hallucinations represented 7.5% of the cases of mild cognitive decline, 21.8% in cases of mild dementia and mild dementia in 28.6% (p = 0.024). Apathy was 15% in mild cognitive decline, 32.7% in mild dementia and 35.7% in moderate dementia (p = 0.046). The disinhibition showed 5.0% in mild cognitive decline, 12.7% in mild dementia and 21.4% in moderate dementia (p = 0.042).Neuropsychiatric symptoms are common in individuals with dementia and tend to increase the prevalence over time of disease progression. The results are consistent with the literature, where the low education is a contributing factor for psychotic symptoms when faced with high education, which is protective for the existence of cognitive decline and its associated symptoms. The increase in years of life contributes to the emergence of BPSD at older ages, as octogenarians, age at which the disease can be in the moderate stage. The evaluation of SCDP at level or evidence, it must be performed in all patients.